Linking Gender Role Orientation to Subjective Career Success: The Mediating Role of Psychological Capital. (May 2014) - Ngo, Hang Yue; Foley, Sharon; Ji, Ming Shuang; Loi, Raymond
This study investigates the relationships among gender role orientation (i.e., masculinity and femininity), psychological capital (PsyCap), and subjective career success. Based on gender role theory, we predict that masculinity has a stronger effect on an individual's job and career satisfaction than femininity does. We also expect that PsyCap mediates the relationships between gender role orientation and the outcome variables. A data set collected from 362 Chinese employees was used to test the hypotheses. The results of regression analyses show that the effect of masculinity on job and career satisfaction is stronger than that of femininity. Additionally, both masculinity and femininity are positively related to an individual's level of PsyCap. The various components of PsyCap, including self-efficacy, hope, and optimism, are found to play different roles in mediating the relationships between gender role orientation and job and career satisfaction.